Respuestas
Respuesta dada por:
2
3(f(x)-3)-4=15x+8
3f(x)-9-4=15x+8
3f(x)-13=15x+8
f(x)=(15x+21)/3
f(x)=5x+7
Reemplazando:
f(4)=5(4)+7
f(4)=20+7
f(4)=27 (Rpta.)
3f(x)-9-4=15x+8
3f(x)-13=15x+8
f(x)=(15x+21)/3
f(x)=5x+7
Reemplazando:
f(4)=5(4)+7
f(4)=20+7
f(4)=27 (Rpta.)
Respuesta dada por:
1
Respuesta:
espero que te ayude
Adjuntos:
![](https://es-static.z-dn.net/files/de4/319ea5859a476424abbd8b4ecf6dacbc.jpg)
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años